Inductors of change in the training of health personnel: pró-saúde and pet-saúde (pro-health and pet-health strategies) - doi: 10.5020/18061230.2012.p393 - Isabel Cristina Luck Coelho de Holanda; Magda Moura de Almeida; Edyr Marcelo Costa Hermeto (Universidade de Fortaleza, 2013)
In the last decade, the training of health professionals has been redesigned in order to meet people's health needs and not just their demands. Public policies on education and health promoted in partnership with the Ministry of Education and Culture (MEC) and the Ministry of Health (Ministério da Saúde - MS) signaled for a curricular reform that is essential to graduate schools in health area(1,2).The milestone in the formalization of this change was the introduction of the National Curriculum Guidelines (Diretrizes Curriculares Nacionais - DCN) for undergraduate programmes in the health field. All current instruments guide theconstruction of the graduates' profile by means of an academic and professional model in which attitudes, skills and contents aim at a generalist, humanist, critical and reflective training, with competence in performance of all levels of health care,basing their conduct on scientific and ethical rigour(3-7).Not coincidentally, all documents point out the same fields of competence to be developed during the training of different professionals: health care, decision making, communication, leadership, lifelong education, administration and management (3-7), since health, being a complex field, is unable to perform resolving actions through a single discipline or area of knowledge.The proposal advocated by MEC and MS to produce transformation in the processes of training, working and expanding the service coverage has been accomplished through induction programmes, such as the Reorientation of Professional Training in Health National Programme (Pro-Health) and the Educationthrough Labour on Health Programme (PET-Health)(1,2).Pro-Health, which has been implemented in the country since 2005, through the disclosure of open announcements, wishes to tune healthcare education and social needs, considering historical, cultural and economic dimensions of the population(8). It encourages discarding the disease as the object of study and moving to focus on the attention to the individual. Its purpose is to train professionals whose profiles have become suitable to the local systems, and that implies promoting the abilities of learning, team work, communication, agility in the face of the situations, proactive and critical ability(9).Pro-Health provided financial inducements linked to partnerships between the State educational institutions and municipal health services. This partnership has led to adaptation of the facilities and provision of new equipments for Health Units that receive students and the teaching and learning activities, as well as to the promotion of spaces for permanent education shared by the academy and thehealthcare establishments.Being contemplated by recent announcements of Pro-Health and PETHealth, the University of Fortaleza (UNIFOR) has instituted a set of changes in undergraduate courses in the health area, starting from the expansion of the practice scenarios into the municipal facilities, the interdisciplinary practices and the adoption of active methodologies in the teaching-learning process, aiming for the determinants of health (promotion, prevention, recovery and rehabilitation).These are covered in all areas of learners' training, in order to enable interventions and integrated actions in which they are considered the subject of the teaching-learning process and seeking knowledge production and provision of services anchored in the principles of the Unified Health System (Sistema Único de Saúde- SUS).In partnership with the Municipal System of School Health (Sistema Municipal de Saúde Escola - SMSE)) of Fortaleza, UNIFOR has been pointing out the need for investments into the Family Health Strategy and in popular health education to be developed by health teams, as recommended by the MS(8). With the support of its ten undergraduate programmes in the health area, UNIFOR has contributed to the inclusion of the extended health team at the Centers for Family Health (Centro de Saúde da Família- CSF) to improve the quality of services, in addition to achievement of the goals that involve full attention and resoluteness. The targeting of educational activities at the so-called 'out of school doors' environment intends to collaborate in interdisciplinary activities.Pro-Health and PET-Health are conferred a differential approach by UNIFOR, due to the interdisciplinary work provided by ten courses in the health area, with the involvement of management and surveillance as integrative and horizontal lines, besides the secondary services of the University itself, linked to the Networks for Health Care (Redes de Atenção à Saúde - RAS), which encourage continuous work, fostering research in areas that are strategic for SUS, qualifying health workers and allowing early initiation of the student in the professional practice.Team work has as its fundamental goal the sharing of knowledge during training, promoting a close association between theory and practice in a contextualized way. Integrality guides the formation of a fairer, ethical and human professional, regardless of the labour market(10).Researches claim that if individuals of various professions learn together, they will work better together and, thus, enhance the attendance and provision of services(11). From this perspective, both programs, Pro-Health and PET- Health, encourage learning tutorial groups in strategic areas for the public health service, providing integrated participation of the undergraduate courses in the area and encouraging interdisciplinary teaching in their own scenario of activities.The scope of the work takes place through interdisciplinary approach to the phenomena that interfere in the health of the population, aiming to achieve greater effectiveness of programmes and services offered to the population(12). The interdisciplinary strategies involve carrying out planned, executed and evaluated activities by all of UNIFOR courses involved in those Programmes, in partnership withThat is, both regarding the undergraduate education, and the research and extension projects, it is understood that the integration between teaching and services must be articulated, including the academy and health services in order to meet the urgent needs and improve health care for the population through better training of service workers (13).The Brazilian Journal for Health Promotion (RBPS), in line with the new policies on health and education, remains reminding us, with its publications, the inextricable connection between teaching, research and extension activities within universities, linking the production of knowledge to the improvement of different local realities of life through the disclosure of experiences and researches that give priority to the intersectoral work, understanding that, nowadays, talk about health also involves the look from the perspective of human resource training.